(3MGTjI Ydi TQM GdebOeI GdQMHjIs - (3EHQGgje Hf eMeO GdHQeGhis; (3HOQ GdOjf CHh GdbGSe eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbj SHW GdeGQOjfj, SHW GdeGQOjfj,J (B907 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ef Ydi GdYdeGA HLRjd aVdg hHYO agPg MGTjI Ydi TQM GdYdGeI GdeGQOjfi bhdg HSe Gddg GdQMef GdQMje jJYdb HgG cdGe ePchQai eMdg s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3hdh Nda RhLJjf hSJ LOGJ hYTQI CNhI dGe hSHYI CYeGe dcGf LRh SgegG eGjJjf hYTQI dJHGjf GdeMahXGJ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B54 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B188s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs